Tracing the Footsteps of Women in the Early Church: Their Role and Disengagement in Church History - Mautuka, Maria Sonya; Aruan, Tiopan (Scriptura Indonesia, 2024)
Women played a crucial role in the development of the early church, yet their tangible contributions have often been ignored or hidden within the official narratives of church history. This article seeks to trace the roles of female congregants such as Phoebe, Priscilla, Lydia, and others who served as house church leaders, ministers, and missionary partners in early Christian communities. Through a historical-critical approach, engagement with primary and secondary literature, and contextual hermeneutical analysis, this study exposes the patriarchal bias embedded in church historiography and offers a theological correction. It is hoped that this research will provide a theological reflection for the contemporary church to be more inclusive of women’s leadership, so that the legacy of early Christian women can inspire today’s church to build a more just and equitable community.